Keselarasan Femininitas dan Maskulinitas dalam Cerpen “The Other Two” Karya Edith Wharton - Ratna Asmarani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This paper analyzes how harmony between femininity and masculinity is achieved in the short story "The Other Two" by Edith Wharton. The short story tells the story of Alice, who has gone through the failure of her previous two marriages and tries hard to maintain her third marriage with Waythorn. To support the analysis that focuses on Alice and the three men in her life uses concepts of femininity and masculinity, including concept understanding, characteristics, and influencing factors. The research method used is a combination of several methods to obtain a comprehensive analysis. The library method with close reading supports the search for textual data. The contextual method borrows the concepts of femininity and masculinity to support the analysis of textual elements of characters, conflicts, and settings, and the analysis is presented qualitatively. The analysis results show that Alice's femininity tends to be flexible, adaptive, and developed to reduce the turmoil that arose in her third marriage with Waythorn. Alice's flexibility of femininity is also able to melt the stiff atmosphere when the three men in Alice's life with their respective masculinities unexpectedly meet at Waythorn-Alice's house.